2006
DOI: 10.1002/esp.1302
|View full text |Cite
|
Sign up to set email alerts
|

Interrill erosion on cultivated Greek soils: modelling sediment delivery

Abstract: For interrill erosion, raindrop-induced detachment and transport of sediment by rainfalldisturbed sheet flow are the predominant processes, while detachment by sheet flow and transport by raindrop impact are negligible. In general, interrill subprocesses are interactively affected by rainfall, soil and surface properties. The objective of this work was to study the relationships among interrill runoff and sediment loss and some selected parameters, for cultivated soils in central Greece, and also the developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…During inter‐rill erosion, soil is mainly detached by raindrop impact, and detached soil particles are transported by the raindrop‐impacted shallow overland flow (Dimoyiannis et al ., ). Yan et al .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…During inter‐rill erosion, soil is mainly detached by raindrop impact, and detached soil particles are transported by the raindrop‐impacted shallow overland flow (Dimoyiannis et al ., ). Yan et al .…”
Section: Resultsmentioning
confidence: 97%
“…Furthermore, several researchers have reported that aggregate stability can be used to establish the soil erodibility factor in erosion prediction equations (e.g. WEPP (Water Erosion Prediction Project), RULSE2 (revised universal soil loss Equation ) (Mbagwu & Auerswald, ; Dimoyiannis et al ., ; Shi et al ., ; Le Bissonnais, ). Mbagwu & Auerswald () obtained an exponential relation between inter‐rill erosion and percolation stability (PS), which is an index of soil aggregate stability based on the amount of water percolated through a column of dry soil aggregates.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Aggregate stability gave the best prediction of erosion. Dimoyiannis et al (2006) tested the hypothesis that a topsoil aggregate instability index of sandy loam to clay soils developed on tertiary calcareous materials and quaternary alluvial deposits and determined by wet sieving technique would fairly account for soil interrill erodibility and, in combination with a rainfall factor, for runoff amount in central Greece. The results showed a significant linear correlation between runoff and the product of instability index of topsoil aggregates and rain kinetic energy (r = 0.80).…”
Section: Soil Erosion Process and Physical Soil Erosion Indicatorsmentioning
confidence: 99%
“…Some researchers thought that using aggregate stability as soil erodibility factor is simpler and more feasible for erosion prediction models (Dimoyiannis et al, 2006;Yan et al, 2010). Both positive and negative correlations between aggregate stability and soil erosion have been reported, largely because these results are mainly obtained from empirical information without considering the different models of aggregate breakdown under different initial conditions (Fox and Le Bissonnais, 1998;Yan et al, 2008).…”
Section: Soilmentioning
confidence: 99%